2015
DOI: 10.1002/jbmr.2719
|View full text |Cite|
|
Sign up to set email alerts
|

Odanacatib Restores Trabecular Bone of Skeletally Mature Female Rabbits With Osteopenia but Induces Brittleness of Cortical Bone: A Comparative Study of the Investigational Drug With PTH, Estrogen, and Alendronate

Abstract: Cathepsin K (CK), a lysosomal cysteine protease, is highly expressed in mature osteoclasts and degrades type 1 collagen. Odanacatib (ODN) is a selective and reversible CK inhibitor that inhibits bone loss in preclinical and clinical studies. Although an antiresorptive, ODN does not suppress bone formation, which led us to hypothesize that ODN may display restorative effect on the osteopenic bones. In a curative study, skeletally mature New Zealand rabbits were ovarectomized (OVX) and after induction of bone lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Osteoporosis is a disease of the bones, in which the rate of bone resorption by osteoclasts exceeds the rate of bone formation by osteoblasts (41). The therapeutic strategy for treating patients with osteoporosis is straightforward: Either decrease the activity of osteoclasts with bisphosphonates and estrogen-associated compounds or increase the activity of osteoblasts with parathyroid hormones (42). Therefore, the agent alendronate acid is widely used to increase bone marrow density in clinics (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a disease of the bones, in which the rate of bone resorption by osteoclasts exceeds the rate of bone formation by osteoblasts (41). The therapeutic strategy for treating patients with osteoporosis is straightforward: Either decrease the activity of osteoclasts with bisphosphonates and estrogen-associated compounds or increase the activity of osteoblasts with parathyroid hormones (42). Therefore, the agent alendronate acid is widely used to increase bone marrow density in clinics (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Here it is of interest that ovariectomized skeletally mature New Zealand rabbits displayed reduced ductility and enhanced brittleness of the central femur after 14 weeks of odanacatib treatment. [158] Other antiresorptive therapies such as bisphosphonate treatment have also been demonstrated to contribute to osteopetrosis-like symptoms in humans. A case of osteopetrosis was described for a 12 year-old child who had received a bisphosphonate treatment for 5 years [159] and numerous bisphosphonateinduced jaw osteonecrosis cases in adults have been discussed as a specific form of chemically induced osteopetrosis.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Furthermore, odanacatib did not impair callus formation or its biomechanical integrity in a rabbit model of fracture healing [ 41 ]. A recent study reported that while odanacatib restored trabecular BMD, microstructure and biomechanical properties, and increased bone formation and cortical thickness of the central femur in osteopenic rabbits, it also led to loss of crystal heterogeneity that appeared to contribute to cortical brittleness [ 42 ]. The latter report, that contrasts all other observations, needs to be confirmed in further studies.…”
Section: Pycnodysostosismentioning
confidence: 99%